INVESTIGASI PROPRIO MOTU TERHADAP PELANGGARAN HUKUM PERANG PADA KONFLIK ISRAEL PALESTINA DALAM OPERATION PROTECTIVE EDGE - Riry Delany; Diah Apriani Atika Sari (BELLI AC PACIS, 2017)
Non-governmental organizations which engaged in international human rights such as Human Rights Watch, found some facts about the violation of the law of war on the armed conflict between Israel and Palestine in a military operation called Operation Protective Edge. A number of Palestinian human rights organizations have collected the facts of the violations and submitted an investigation request to the ICC. Under Article 13 of the Rome Statute 1998, the International Criminal Court (ICC) or the International Criminal Court has three forms of authority to examine a dispute. One of them is through the initiative of the ICC Prosecutor or known as proprio motu. This paper will examine the issues in the request for investigation of proprio motu on alleged violations of the war committed by Israel.